Information and Communication Technology Waste Management Systems in Academic Libraries in Delta State, Nigeria - Ogbomo, Monday Obaidjevwe (MiddleBelt Journal of Library and Information Science, 2014)
Information and Communication Technology (ICT) tools are deployed in academic libraries to acquire process, disseminate and use of information. However, as the ICT tools deteriorate, there emerges an environmental concern called e-waste. This study investigated ICT wastes management systems in academic libraries in Delta State, Nigeria. The survey research design was adopted for the study. The entire population of 14 system librarians was studied. Data were collected with the use of questionnaire and analysed using frequency count. The results show that 941 ICT wastes were generated from 2002 to 2012 in academic libraries in Delta State, ICT wastes were kept in stores, landfilling and reuse as the disposal methods adopted. Also the study found that there was no policy on ICT waste management. The study concluded that ICT wastes were generated in academic libraries without appropriate policy on their proper management. It was recommended that the libraries should develop policies on ICT waste management in line with existing e-waste laws in Nigeria and implement same to ensure healthy and eco-friendly environment.